2014
DOI: 10.3897/zookeys.371.6580
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the Rhinella margaritifera species group (Anura, Bufonidae) from the montane forest of the Selva Central, Peru

Abstract: We describe a new species of the bufonid toad genus Rhinella from transition montane forest of the buffer zones of the Yanachaga-Chemillén National Park and the Pui Pui Protected Forest (eastern slopes of Andes, Selva Central, Peru). The new species belongs to the Rhinella margaritifera species group (confirmed by mtDNA data) and differs from all its members by the absence of tympanic membrane and tympanic annulus. It is characterized by medium size (SVL 57.5–65.5 mm, n = 5), moderately developed cranial crest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…Trueb (1971) noted the external similarity between the R. margaritifera and R. acrolopha groups, and recent phylogenetic analyses have supported a close relationship between them (e.g., Frost et al, 2006). However, molecular evidence indicates an even closer relationship between the R. acrolopha group and certain species of the R. veraguensis group, specifically R. chavin, R. manu, R. nesiotes, and R. yanachaga (Pramuk, 2006;Chaparro et al, 2007;Pramuk et al, 2008;Van Bocxlaer et al, 2010;Pyron and Wiens, 2011;Peloso et al, 2012;Moravec et al, 2014). Furthermore, the results of those analyses of DNA sequences are consistent with the distribution of several putative morphological synapomorphies, including: (1) occurrence of few, large, unpigmented eggs in the R. acrolopha group and R. chavin, R. justinianoi, R. manu, R. multiverrucosa, R. nesiotes, and R. yanachaga of the R. veraguensis group (Duellman and Toft, 1979;Lehr et al, 2001Lehr et al, , 2005Lehr et al, , 2007Chaparro et al, 2007); (2) m. levator mandibulae externus undivided with trigeminal nerve passing medial (deep) to the muscle in R. paraguas (reported herein) and all other species of the R. acrolopha group (TG, personal observation) and at least R. manu (Chaparro et al, 2007) and R. quechua (TG, personal observation) of the R. veraguensis group; and (3) absence of the m. adductor longus in the R. acrolopha group (Trueb, 1971; TG, personal observation) and R. manu (Chaparro et al, 2007).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Trueb (1971) noted the external similarity between the R. margaritifera and R. acrolopha groups, and recent phylogenetic analyses have supported a close relationship between them (e.g., Frost et al, 2006). However, molecular evidence indicates an even closer relationship between the R. acrolopha group and certain species of the R. veraguensis group, specifically R. chavin, R. manu, R. nesiotes, and R. yanachaga (Pramuk, 2006;Chaparro et al, 2007;Pramuk et al, 2008;Van Bocxlaer et al, 2010;Pyron and Wiens, 2011;Peloso et al, 2012;Moravec et al, 2014). Furthermore, the results of those analyses of DNA sequences are consistent with the distribution of several putative morphological synapomorphies, including: (1) occurrence of few, large, unpigmented eggs in the R. acrolopha group and R. chavin, R. justinianoi, R. manu, R. multiverrucosa, R. nesiotes, and R. yanachaga of the R. veraguensis group (Duellman and Toft, 1979;Lehr et al, 2001Lehr et al, , 2005Lehr et al, , 2007Chaparro et al, 2007); (2) m. levator mandibulae externus undivided with trigeminal nerve passing medial (deep) to the muscle in R. paraguas (reported herein) and all other species of the R. acrolopha group (TG, personal observation) and at least R. manu (Chaparro et al, 2007) and R. quechua (TG, personal observation) of the R. veraguensis group; and (3) absence of the m. adductor longus in the R. acrolopha group (Trueb, 1971; TG, personal observation) and R. manu (Chaparro et al, 2007).…”
Section: Methodsmentioning
confidence: 98%
“…Moravec et al (2014) found R. festae to be nested between R. nesiotes and R. chavin þ R. yanachaga and proposed the R. festae group for those species and R. macrorhina and R. rostrata (not included in their analysis). DNA sequences are available for only 3 of the 10 R. acrolopha group species and 6 of the 19 R. veraguensis group species, however, and Moravec et al (2014) did not address any species of the R. acrolopha group or R. veraguensis group that have not been sequenced. Pramuk (2006), Chaparro et al (2007), and Van Bocxlaer et al (2010) found the nearest relatives of the R. acrolopha group to form a grade, whereas Pyron and Wiens (2011) found them to form a clade.…”
Section: Methodsmentioning
confidence: 99%
“…Rhinella sebbeni sp. nov. is distinguished from R. yunga by its snout being mucronate in dorsal view (vs. slightly pointed), tympanic membrane and tympanic annulus present (vs. absent), bony protrusion at the angle of jaws poorly developed (vs. undeveloped), vestigial webbing in toes (vs. developed), and by its cephalic crests being well-developed (vs. poorly developed; Moravec et al 2014).…”
Section: Species Descriptionsmentioning
confidence: 99%
“…Fouquet et al (2007a) also excluded R. cristinae, R. sternosignata, R. iserni, and R. ceratophrys from the R. margaritifera group as these species do not possess morphological synapomorphies proposed by Vé lez-Rodriguez (2004, as cited in Fouquet et al 2007a): the depressor mandibulae muscle formed by two slips, and the presence of a thickening on the ventrolateral border of the quadratojugal that can be seen as a process on the extreme forms. Accordingly, we recognize the following species in the R. margaritifera species group (Moravec et al 2014): Rhinella acutirostris (Spix 1824), Rhinella alata (Thominot 1884), R. castaneotica (Caldwell 1991), Rhinella dapsilis (Myers and Carvalho 1945), Rhinella hoogmoedi Herein we describe two new species of Rhinella from two Brazilian biomes: one occupying dry forested areas of the Cerrado in central Brazil and another from Amazonian rain forest. Both species are currently allocated in the R. margaritifera species group based on their having an expansion of the posterior ramus of the pterygoid (see Pramuk 2006), and also by a combination of other morphological features.…”
mentioning
confidence: 95%
See 1 more Smart Citation